Long-Term and Seasonal Variability of Wind and Wave Extremes in the Arctic Ocean - Isabela S. Cabral; Ian R. Young; Alessandro Toffoli (Frontiers in Marine Science, 2022)
Over recent decades, the Arctic Ocean has experienced dramatic variations due to climate change. By retreating at a rate of 13% per decade, sea ice has opened up significant areas of ocean, enabling wind to blow over larger fetches and potentially enhancing wave climate. Considering the intense seasonality and the rapid changes to the Arctic Ocean, a non-stationary approach is applied to time-varying statistical properties to investigate historical trends of extreme values. The analysis is based on a 28-year wave hindcast (from 1991 to 2018) that was simulated using the WAVEWATCH III wave model forced by ERA5 winds. Despite a marginal increase in wind speed (up to about 5%), results demonstrate substantial seasonal differences and robust positive trends in extreme wave height, especially in the Beaufort and East Siberian seas, with increasing rates in areal average of the 100-year return period up to 60%. The reported variations in extreme wave height are directly associated with a more effective wind forcing in emerging open waters that drives waves to build up more energy, thus confirming the positive feedback of sea ice decline on wave climate.